PENGARUH ORGANISASI PRIGMA TERHADAP PEMAHAMAN AGAMA MASYARAKAT DESA GUNUNG MULYA KABUPATEN BOGOR - Elza Fauziah Safitri; Kholil Nawawi; Abristadevi Abristadevi (KOLONI, 2022)
Islam has regulated human behavior in meeting the needs of life, namely not deviating from the teachings of Islam. Religious maturity towards the community is seen in the ability of community members to understand, appreciate and apply the noble values ​​of their religion in their daily lives. One way that can be used to help people who deviate from the teachings of Islam is the existence of a group of people or organizations that hold religious community activities such as weekly recitations. Through this religious activity, it is expected to be able to improve the understanding of the community's Islamic religion correctly in accordance with the Qur'an and the Sunnah of the Prophet Muhammad. This study aims to determine the influence of the organization on the religious understanding of the people of Gunung Mulya Village, Bogor Regency. This study uses a quantitative approach with survey techniques. The variables in this study are the prigma organization as the independent variable and the religious understanding of the community as the dependent variable. The population is the people of Gunung Mulya Village, Bogor Regency, which consists of 30 people. Based on the results of data analysis that has been carried out, it is obtained a simple linear regression equation model Y = 26.602 + 0.415X, which means that the prigma organization has a positive effect on the religious understanding of the people of Gunung Mulya Village. In the t-test obtained a significant value of 0.002 <significant level 0.05, thus the hypothesis is declared accepted. The result of the coefficient of determination R2 = 0.295 which indicates that the prigma organization affects the religious understanding of the community by 29.5%, while the remaining 70.5% is influenced by factors other than the prigma organization. Keywords: Organization, Community Religion Understanding